2012
DOI: 10.1021/jp212440f
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Pore Size and Pore Loading on Structural and Dynamical Heterogeneities of an Ionic Liquid Confined in a Slit Nanopore

Abstract: Molecular dynamics simulations were performed to investigate the structural and dynamical properties of varying amounts of the ionic liquid (IL) [EMIM + ][TFMSI − ] confined inside slit-like graphitic pores of different widths, H. The ions distributed in layers inside the slit pores, with the number of layers depending on pore size. A reduction in pore loading leads to the formation of regions of high and low density of ions in the center of the pore. Variations in pore size and pore loading seem to induce onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
181
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(217 citation statements)
references
References 101 publications
32
181
4
Order By: Relevance
“…For example, some researchers have applied small-amplitude techniques such as impedance spectroscopy [57][58][59][60][61][62][63][64][65][66][67][68][69][70], while others have applied large-amplitude techniques such as cyclic voltammetry [71][72][73][74][75][76][77]. A few pioneers have even performed computer simulations [78][79][80][81][82][83][84][85][86][87][88][89][90]. In spite of these diverse efforts, however, no single model has yet emerged that is capable of rationalizing the whole gamut of experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some researchers have applied small-amplitude techniques such as impedance spectroscopy [57][58][59][60][61][62][63][64][65][66][67][68][69][70], while others have applied large-amplitude techniques such as cyclic voltammetry [71][72][73][74][75][76][77]. A few pioneers have even performed computer simulations [78][79][80][81][82][83][84][85][86][87][88][89][90]. In spite of these diverse efforts, however, no single model has yet emerged that is capable of rationalizing the whole gamut of experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the simulation details and methods are exactly the same as those used in our previous studies. [50,[63][64][65][66][67][68] …”
Section: Methodsmentioning
confidence: 99%
“…This is the new finding of the present study. Rajput et al 5 reported that the diffusion coefficients of EMI + and TFSI ¹ show the monotonically decrease behavior with decreasing pore size. They examined the pore size over 1.9 nm.…”
Section: Tfsimentioning
confidence: 99%
“…Later, Feng and Cummings 4 found another capacitance peak around 1.4 nm pore size by molecular dynamics (MD) calculations, and suggested oscillatory behavior of capacitance as a function of pore size. Rajput et al 5 examined the effects of slit pore size and pore loading on the properties of ILs by MD calculations. However, the relationship between oscillatory behavior of capacitance and dynamics of ILs has not properly been explained.…”
Section: Introductionmentioning
confidence: 99%